Linked color imaging provides enhanced visibility with a high color difference in upper gastrointestinal neoplasms. Issue 1 (13th October 2022) - Dohi, Osamu; Ono, Shoko; Kawada, Kenro; Kitamura, Shinji; Hatta, Waku; Hori, Shinichiro; Kanzaki, Hiromitsu; Murao, Takahisa; Yagi, Nobuaki; Sasaki, Fumisato; Hashiguchi, Keiichi; Oka, Shiro; et al.
Abstract: Background and Aim: The aim of this post‐hoc analysis in a randomized, controlled, multicenter trial was to evaluate the visibility of upper gastrointestinal (UGI) neoplasms detected using linked color imaging (LCI) compared with those detected using white light imaging (WLI). Methods: The visibility of the detected UGI neoplasm images obtained using both WLI and LCI was subjectively reviewed, and the median color difference (Δ E ) between each lesion and the surrounding mucosa according to the CIE L*a*b* color space was evaluated objectively. Multivariate logistic regression analysis was performed to identify factors associated with neoplasms that were missed under WLI and detected under LCI. Results: A total of 120 neoplasms, including 10, 32, and 78 neoplasms in the pharynx, esophagus, and stomach, respectively, were analyzed in this study. LCI enhanced the visibility 80.9% and 93.6% of neoplasms in pharynx/esophagus and stomach compared with WLI, respectively. LCI also achieved a higher Δ E of enhanced neoplasms compared with WLI in the pharynx/esophagus and stomach. The median WLI Δ E values for gastric neoplasms missed under WLI and later detected under LCI were significantly lower than those for gastric neoplasms detected under WLI (8.2 vs 9.6, respectively). Furthermore, low levels of WLI Δ E (odds ratio [OR], 7.215) and high levels of LCI Δ E (OR, 22.202) were significantly associated with gastric neoplasms missed under WLI and later detected under LCI. Conclusion: Color differences were independently associated with missing gastric neoplasms under WLI, suggesting that LCI has an obvious advantage over WLI in enhancing neoplastic visibility.